RECCURENT LARYNGEAL PAPILLOMA - Purnami, Nyilo; Fathoni, Rizka (Indonesian Journal of Tropical and Infectious Disease, 2012)
A case of respiratory papillomatosis was reported. The patient suffered from the disease since eight months old with chief complaint progressive hoarseness and dyspnea. It was diagnosed with respiratory papillomatosis and scheduled for performing tracheotomy and continued with the first microlaryngeal surgery (MLS). Decanulation was taken after 2nd surgery of removing papillomas. Finally was reported she got serial of surgery for 22 times during 18 years of age. It was costly and deteriorating quality of life. The problem remains persisted because of frequent recurrences and need for repetitive surgeries. Specimen biopsy for histologic examination was shown the signs of HPV infection, papilomatic coated squamous epithel with mild dysplasia and coilocytosis. The threatening of upper airway obstruction is the main important reason for patients coming. The patency of airway assessed by Direct Laryngoscopy then the next treatment was decided with schedule of Micro Laryngeal Surgery (MLS). Finally the MLS treatment is just only for temporarilyrecovery. A further research to define the proper treatment in the future is required, especially for prevention of the diseases related to the viral causes of infection.